INDIVIDUAL VALUE SYSTEM CHARACTERISTICS AND DRIVING BEHAVIOR RELATIONSHIPS - Lazdiņš, Krists Jānis; Mārtinsone, Kristīne (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The aim of research was to examine characteristics of individual value system prediction for driving behavior. It raised fundamental question for the research: 1. which of the individual value system characteristics predict driving behavior controlling gender and age.In the study participated 108 respondents, 40 (37.0%) men and 68 (63.0%) women who filled the questionnaire on the internet. There was used two questionnaires – „Latvian driving behavior survey”, The value and levels of availability relations in different spheres of life”The results showed that the value system integrity / disintegrity indicator predicts distracted driving, explains 18% of variation and is statistically significantly. Internal vacuum and age statistically significantly negatively predicts risky driving explaining 17% of variation. Age statistically significantly predicts safe and courteous driving, explains 12% of variation. Value system integrity / disintegrity indicator and gender, statistically significantly negatively predicts summary indicator of dangerous driving, explains 22% of variation. Age statistically significantly negatively predicts distracted driving, explains 30% of variation.Limitations of the research are related to the size of the sample, alignment of participants and use of new instruments, as well as data collection method. If the study would be repeated in the future, it would be desirable to increase the sample size and use approbated instrument. It would be interesting to find out how the value of individual factors predicts objective size of accidents and violations caused by driving.The results can serve as the basis to create new driving behavior interventions and also applicable to psychologist's professional work, when counseling individuals of this group, as well as can be used in the future development of the field, science and research.